2012
DOI: 10.1002/ijc.27828
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of persistent genital human papillomavirus infection among women worldwide: A literature review and meta-analysis

Abstract: Persistent high-risk human papillomavirus (HR-HPV) infection is the strongest risk factor for high-grade cervical precancer. We performed a systematic review and meta-analysis of HPV persistence patterns worldwide. Medline and ISI Web of Science were searched through January 1, 2010 for articles estimating HPV persistence or duration of detection. Descriptive and meta-regression techniques were used to summarize variability and the influence of study definitions and characteristics on duration and persistence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
165
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 109 publications
8
165
1
4
Order By: Relevance
“…The propensity for certain genotypes to persist longer than others (Rositch et al, 2013) may contribute to the observed HPV genotype distribution differences between low-grade disease and cervical cancer (Guan et al, 2012).…”
Section: Received 5 November 2014 Accepted 12 March 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity for certain genotypes to persist longer than others (Rositch et al, 2013) may contribute to the observed HPV genotype distribution differences between low-grade disease and cervical cancer (Guan et al, 2012).…”
Section: Received 5 November 2014 Accepted 12 March 2015mentioning
confidence: 99%
“…Although the proportions of individuals were similar between the HPV16 and HPV51 NI status categories, neutralizing antibody titres against HPV16 tended be higher than those against HPV51. This may indicate true differences in the host response to infection between these genotypes and differences in persistence (Rositch et al, 2013) and/or highlight subtle differences in the ability of HPV pseudoviruses to mimic their archetypal strain.These data improve our understanding of a little-studied oncogenic HPV genotype, HPV51, and demonstrate the importance of selecting representative HPV sequences, including consideration of variation in both the major and minor capsid proteins, for the construction of appropriate antigens. These data also corroborate recent observations of poor concordance between the VLP ELISA and the pseudovirus neutralization assay for measuring NI antibodies (Safaeian et al, 2012) in contrast to the generally good concordance for measuring vaccine-induced typespecific antibody (Dessy et al, 2008;Krajden et al, 2014).…”
mentioning
confidence: 99%
“…According to multiple studies, the status of HPV infection may be incident (which is negative at start of study "baseline" and become positive after that), persistent (detecting the same HPV type at 2 or more examinations 6 month apart), multiple, or high risk infection (12,13) .…”
Section: Materials and Methods:-mentioning
confidence: 99%
“…Some disease processes are dependent on both the current state of the system and its history [14]. The classic SIR model cannot accomodate this; however, the age-structured models of Kermack and McKendrick [2,3] can model such diseases.…”
Section: Introductionmentioning
confidence: 99%